Implementation of Standardized Patient in Nursing Education - Soivong, Pratum; Suksatit, Benjamas; Khampolsiri, Totsaporn; Suwankruhasn, Nattaya (Nursing Research and Innovation Journal, 2016)
The standardized patient (SP) is a healthy individual or an actual patient who trained to portray the roles of patient. The objective of using SP was to encourage the learners to learn and practice on required skills through the realistic interaction between the learner and SP without any harm or risk to the actual patient. SP is found to be an excellent teaching method to facilitate effective communication skills, promote students’ confidence, skills and ability to perform physical examination, help students to use critical thinking skills, and assist them to overcome their feelings of nervousness and anxiety. This article also discusses issues to be considered when integrating SP program into nursing curriculum. This article presents an example of implementing SP in practicum class for the junior nursing students aimed to provide care for patients with cancer. Thirty-six nursing students participated in this class. After the class, the majority of students reported that they had good level of knowledge related to nursing care for patients with cancer. More than ninety percent of students informed that they were confident to apply the acquired knowledge to practice. Additionally, ninety-seven percent expressed high level of satisfaction with the SP method. The learners also expressed that they were impressed and enjoy with the method of teaching of integrating SP. They gain direct experience in providing nursing care to the SP as the real situation and they have learned to be aware of the patients’ feeling.